Effect of Seaweed Ethanol Extract on Cholesterol Levels and Obesity in White Rats - Syafika Alaydrus; Magfirah; Indah Kurnia Utami (Tropical Biopharmaca Research Center, IPB University, 2020)
Seaweed (EucheumaCottonii J. Agardh) is one of the biological resources found in coastal and marine areas. Seaweed contains secondary metabolites such as flavonoids, alkaloids, polyphenols and tannins which can reduce cholesterol levels in the blood. This study aims to determine the effect of seaweed ethanol extract on reducing cholesterol and obesity levels by comparing plasma cholesterol levels, body weight, and weight of vital organs (liver, kidneys and jantumg) of obese rats, mice given seaweed ethanol extract with normal mice . Rats were grouped randomly into 6 groups. group one was given 0.5% CMC Na, group two was given high fat diet food, group three was given simvastatin, group four was given seaweed ethanol extract 100 mg / kgbb, group five was given ethanol extract of seaweed 200 mg / kgbb and group six was given ethanol extract of seaweed 300 mg / kg with a long suspension of extract for 14 days. Measurement of cholesterol levels in the blood using the CHOD-PAP method, body weight and organs carried out by weighing. The results showed that seaweed ethanol extract has the effect of inhibiting an increase in plasma cholesterol levels and has anti-obesity potential at a dose of 300 mg / kgbb.